Evaluasi Pemungutan Retribusi Terhadap Pendapatan Asli Daerah (PAD) di Kota Palangka Raya - Farid Zaky Yopiannor; Eka A Mera (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
This study aims to find out and describe and evaluate the collection of market restitution on PAD in the City of Palangka Raya. This study uses qualitative research methods, where researchers are more on observation, and describe the phenomenon of existing problems through words, images. The results of this study indicate that there needs to be an evaluation of the collection of market levies on regional original income (PAD) in the city of Palangka Raya. Either from the input, process, output, and outcomes. In order for the realization of Market Retribution to reach the expected target and the market contribution to regional original income (PAD) is greater.